The Influence of Teamwork and Work Discipline towards Employees’ Performance - Reinaldi, Rizki; Hendri, Edduar; Novalia, Nurkardina (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to investigate the influence of teamwork and work discipline towards the employees’ performance at PT. Haleyora Power, Ogan Ilir Area. The population of this research was all the employees of PT. Haleyora Power, Ogan Ilir Area that was 50 employees. All members of the population were selected as the sample by using non-probability sampling technique with saturated sampling. The method of this study was quantitative method with ex-post facto research design. Multiple linear regression analysis and coefficient of determination were used to analyze the data. Based on the results, it can be concluded that there is significant influence of teamwork on employees’ work performance, there is significant influence of work discipline on employees’ work performance, and there is simultaneous influence between teamwork and work discipline toward employees’ work performance at PT. Haleyora Power, Ogan Ilir Area.